PENGARUH PENGAWASAN, KOMITMEN PEGAWAI DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA TANJUNGBALAI - Rima Wulandari; Suwito .; Zulfitri Syawaluddin Hasibuan; Evan Botung Daulay; Adi Kuncoro (Manajemen dan Bisnis, 2021)
The formulation of the problem in this study are: How do supervision, employee commitment and work environment influence employee work productivity. This study aims to examine how the influence of supervision, employee commitment and work environment on employee work productivity. With total sampling technique, the sample in this study amounted to 35 people. Supervision variables partially have a positive effect on employee work productivity. Employee commitment   variable   partially   has   a   positive   effect   on   employee   work productivity. Work environment variables partially have a positive effect on employee  work productivity.  Supervision  variables,  employee  commitment  and work  environment  simultaneously   have  a  positive  and  significant  effect  on employee work productivity.